Analisis Dakwah Ustaz Irfan Rizki Haas di Media Sosial TikTok - Jaza, Fandi Khusnul; Makrufi, Anisa Dwi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2024)
This study aims to analyze the da'wah (Islamic preaching) methods employed by Ustaz Irfan Rizki Haas on the TikTok platform to engage the younger generation. The study adopts a mixed-methods approach, combining quantitative data collection through Google Form questionnaires and qualitative analysis through content analysis of TikTok posts on @IrfanRizkiHaas and interviews. The findings indicate that da'wah on TikTok is effective in reaching young audiences through an interactive, relevant, and easily understood communication style. Ustaz Irfan Rizki Haas utilizes TikTok features such as Q&A sessions and live streaming to enhance engagement with his followers. Consistent content aligned with contemporary issues fosters positive two-way communication. The implications of this study highlight the importance of adapting da'wah to the digital era and its contribution to the development of modern Islamic communication methods, particularly in engaging younger generations through short-form video-based social media platforms.